Formulation and Physical Stability Test of Aloe vera Hydrogel Eye Mask (Aloe vera (L.) Burm.f.) as Brightening Using Skin Analyzer - Kanne Dachi; Linda Margata; Cut Faranisyah; Dini Pitriyani; Putri Maria Waruwu (Jurnal FARMASIMED (JFM), 2025)
Background: Hydrogel mask is a type of preventive cosmetic, to prevent skin problems, protect and maintain the skin. Hydrogel eye mask is a type of eye mask with easy to stick and remove use, providing a cooling sensation around the skin around the eye area. Aloe vera  gel (Aloe vera  (L.) Burm.f.) can moisturize and brighten the skin, and contains secondary metabolite compounds that inhibit the tyrosinase enzyme. Objective: This study aims to formulate Aloe vera  gel (Aloe vera  (L.) Burm.f.) in the form of a hydrogel eye mask as a brightening using a skin analyzer. Method: This study used an experimental method with concentrations of 0% (blank), 0,5% (F1), 1% (F2), and, 1,5% (F3). Result: Phytochemical screening of Aloe vera  gel (Aloe vera  (L.) Burm.f), irritation test, physical evaluation of the preparation before the cycling test, namely homogeneity, elasticity, adhesiveness, and after the cycling test, namely organoleptic and pH, as well as effectiveness as a brightening using a skin analyzer. The results of 200 mL of Aloe vera  gel extract (Aloe vera  (L.) Burm.f.) contain alkaloids, flavonoids, saponins, tannins, glycosides, and steroids/triterpenoids. The preparation does not cause irritation, and is homogeneous. Blank elasticity:30,11%, F1:31,58%, F2:32,99%, and F3:33,67% with the condition 30-115%. Blank adhesion:6,13 seconds, F1:7,19 seconds, F2:9,18 seconds, and F3:12,11 seconds with the condition >4 seconds. After the cycling test there was no change in color, odor, and shape. pH Blank:6,43, F1:6,41, F2:6,14, and F3:6,10 with the requirement of 4,5-6,5 and the brightening effectiveness test on the skin analyzer experienced an increase in recovery of 32,59% in water content, elasticity of 36,81%, and a decrease in melanin of 29,87% for 4 weeks and the best formula is F3.  Conclusion: Aloe vera  gel extract (Aloe vera  (L.) Burm.f.) can be formulated into a hydrogel eye mask preparation with good physical quality and does not cause irritation.